PENGARUH INVENTORY INTENSITY, KOMISARIS INDEPENDEN, DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK - Wirdha, Latifah Aulia; Isnaeni, Fil (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This research aims to determine the effect of inventory intensity, independent commissioners, and company size on tax aggressiveness in consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The type of research used is a quantitative approach with secondary data. The population of this study consists of 165 companies, with a sample of 15 companies. The data analysis was carried out using E-Views 12 software. The research results show that inventory intensity, independent commissioners, and company size jointly affect tax aggressiveness. However, inventory intensity has a negative effect on tax aggressiveness, while independent commissioners and company size do not have a significant effect on tax aggressiveness